Human-robot interaction in construction: a literature review automation in construction / Mohammad Hossein Ghasempourabadi and Masoume Taraz - Ghasempourabadi, Mohammad hossein; Taraz, Masoume (Universiti Teknologi MARA, Perak, 2021)
This research presents a systematic review of the state-of-the-art research for interaction/ cooperation between humans and robots (HRI/ HRC) in construction considering different types of robots. This paper represents, investigates, and further discusses the different domains of studies in terms of systems, metrics, and types of interactions and types of relative construction possibilities. The main goal of this research is to understand which type of relationship is studied in construction research and whether they have considered the interaction of humans and robots in construction. Also, it will identify the future of robotic construction and communication with humans in the research.